2005
DOI: 10.1016/s0140-6736(05)67528-9
|View full text |Cite
|
Sign up to set email alerts
|

Secondary prevention of macrovascular events in patients with type 2 diabetes in the PROactive Study (PROspective pioglitAzone Clinical Trial In macroVascular Events): a randomised controlled trial

Abstract: SummaryBackground: Patients with type 2 diabetes are at high risk of fatal and non-fatal myocardial infarction and stroke. There is indirect evidence that agonists of peroxisome proliferator-activated receptor 7 (PPAR 7) could reduce macrovascular complications. Our aim, therefore, was to ascertain whether pioglitazone reduces macrovascular morbidity and mortality in high-risk patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

80
2,696
16
163

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 3,822 publications
(2,955 citation statements)
references
References 19 publications
80
2,696
16
163
Order By: Relevance
“…The PROactive trial found a non‐significant 10% reduction in the primary outcome associated with a 0.5% reduction in HbA1c achieved with randomization to pioglitazone in a high‐CV‐risk population with type 2 diabetes but without heart failure 1; this outcome is similar to our MACE+ composite. In the PROactive and CREDIT studies, the benefits of good HbA1c values with regard to CV risk were greater for MACE than MACE+ (MACE being driven only by disease status, and MACE+ also including clinical interventions).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The PROactive trial found a non‐significant 10% reduction in the primary outcome associated with a 0.5% reduction in HbA1c achieved with randomization to pioglitazone in a high‐CV‐risk population with type 2 diabetes but without heart failure 1; this outcome is similar to our MACE+ composite. In the PROactive and CREDIT studies, the benefits of good HbA1c values with regard to CV risk were greater for MACE than MACE+ (MACE being driven only by disease status, and MACE+ also including clinical interventions).…”
Section: Discussionsupporting
confidence: 66%
“…The relationship between glycaemic control and cardiovascular (CV) outcome remains uncertain, with recent randomized trials giving contradictory results 1, 2, 3, 4. Observational studies can provide insights that may be generalized to clinical populations 5.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to black box warnings for both glitazones. The absolute risk is small, amounting to 0.5% compared to 0.1% for placebo in the DREAM trial of rosiglitazone, 49 6% compared to 4% in the PROactive trial 47 of pioglitazone, and a doubling of relative risk upon meta-analysis. 50 One analysis suggests that even when symptoms occur, they tend to be relatively welltolerated.…”
Section: Adverse Effects Of Glitazonesmentioning
confidence: 92%
“…Unlike rosiglitazone, pioglitazone has not been associated with increased risks of cardiovascular events or mortality. The prospective, placebo-controlled PROactive trial of 5,238 subjects with diabetes and known cardiovascular disease demonstrated no increase in risk 47 nor did a subsequent meta-analysis that included the PROactive data as well as other data. 48 The PROactive trial has been criticized for being too stringent in its endpoints and post-hoc reanalysis specifically for major adverse cardiovascular events suggests that the drug reduces the risk of cardiovascular disease.…”
Section: Adverse Effects Of Glitazonesmentioning
confidence: 99%
See 1 more Smart Citation